2022
DOI: 10.1155/2022/7202837
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 Modulates Senescence and Paracrine Action in Placental Mesenchymal Stem Cells via Inhibiting Hedgehog Signaling Pathway in Preeclampsia

Abstract: Preeclampsia (PE) is a heterogeneous disease closely associated with the accelerated senescence of the placentas. Placental mesenchymal stem cells (PMSCs) modulate placental development, which is abnormally senescent in PE together with abnormal paracrine. Both pivotal in the placenta development, Toll-like receptor 4 (TLR4) and Hedgehog (HH) pathway are also tightly involved in regulating cellular senescence. This study was aimed at demonstrating that TLR4/HH pathway modulated senescence of placentas and PMSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…PMSCs expressed common MSCs markers (CD44, CD73, CD90, and CD105) but not CD31, CD34, CD45 (Fig. 1 C) [ 38 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…PMSCs expressed common MSCs markers (CD44, CD73, CD90, and CD105) but not CD31, CD34, CD45 (Fig. 1 C) [ 38 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The findings suggest a strong interaction between P53 and TLR proteins, regulating various cellular processes such as DNA repair and replication, CS, differentiation, cell cycle arrest and tumour dynamics 34 . Studies have shown that overexpression of TLR4 can induce CS in osteocytes, placental mesenchymal cells and dental pulp stem cells 35–38 . TLR2 and TLR5, drove CS of MSCs 39 …”
Section: Discussionmentioning
confidence: 99%
“…34 Studies have shown that overexpression of TLR4 can induce CS in osteocytes, placental mesenchymal cells and dental pulp stem cells. [35][36][37][38] TLR2 and TLR5, drove CS of MSCs. 39 We found eight overlapping hub genes, including TP53, SRC, SIRT1, CCND1, EZH2, CXCL8, AR and CDK4.…”
Section: Discussionmentioning
confidence: 99%
“…The cfDNA profile in C EPE model contained eight genes, of which pTSS coverages of FOSL2 , CAMKK2 , CCND1 , ITPR1 , PRKACB , WNT7B , CACNB2 and NRF1 genes were stably differential between pregnant women with early-onset PE and healthy controls. CAMKK2 , CCND1 , ITPR1 , PRKACB and WNT7B genes were enriched in more than two pathways associated with PE, including “Hedgehog signaling pathway” ( 35 ), “Hippo signaling pathway” ( 36 ), “AMPK signaling pathway” ( 37 ), “Apelin signaling pathway” ( 38 ), “Autophagy” ( 39 ), “Oxytocin signaling pathway” ( 40 ), “Wnt signaling pathway” ( 41 ) and “VEGFA-VEGFR2 signaling” ( 42 ). The AMPK signaling pathway has been repeatedly reported to be associated with PE based on omics data ( 37 , 43 ).…”
Section: Discussionmentioning
confidence: 99%